2020
DOI: 10.3892/ijo.2020.4987
|View full text |Cite
|
Sign up to set email alerts
|

Although c‑MYC contributes to tamoxifen resistance, it improves cisplatin sensitivity in ER‑positive breast cancer

Abstract: Tamoxifen (TAM) resistance is a major challenge in the treatment of estrogen receptor-positive (ER +) breast cancer. To date, to the best of our knowledge, there are only a few studies available examining the response of patients with TAM-resistant breast cancer to chemotherapy, and the guidelines do not specify recommended drugs for these patients. In the present study, TAM-resistant cells were shown to exhibit increased proliferation and invasion compared with the parent cells, and the increased expression o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 63 publications
0
15
0
Order By: Relevance
“…Although the gene effect data based on CRISPR for BT-474 are not available in the DepMap portal, high dependency on ESR1, MYC and CCND1 for cell viability of BT-474 are expected. ER, c-Myc, and Cyclin D1 are also known to promote tamoxifen resistance [ 15 ]. Notably, high MYC and CCND1 expression also correlates with poor relapse-free survival in BC patients treated with endocrine therapies (though it should be noted that the results for CCND1 are not as statistically significant as those for MYC, Figure S3A,B ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Although the gene effect data based on CRISPR for BT-474 are not available in the DepMap portal, high dependency on ESR1, MYC and CCND1 for cell viability of BT-474 are expected. ER, c-Myc, and Cyclin D1 are also known to promote tamoxifen resistance [ 15 ]. Notably, high MYC and CCND1 expression also correlates with poor relapse-free survival in BC patients treated with endocrine therapies (though it should be noted that the results for CCND1 are not as statistically significant as those for MYC, Figure S3A,B ).…”
Section: Resultsmentioning
confidence: 99%
“…Significantly, ER, c-Myc, and Cyclin D1 are known to play roles in driving tamoxifen resistance in BC cells in vitro and in patients. Indeed, tamoxifen-resistant BC cell lines have elevated expression of ER, c-Myc, and Cyclin D1 and inhibition of MYC restores tamoxifen sensitivity in these cells [ 15 ]. High MYC expression also correlates with poor relapse-free survival in patients treated with endocrine therapies [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…c-MYC is known to be over expressed in breast cancer, and its involvement in glutamine uptake and degradation is well reported, as it stimulates surface transporters and glutamine synthetase suppression 29 . Chen et al reported that MCF-7 tamoxifen resistant model produced by treating the cells with increased concentrations of 4-hydroxytamoxifen for 8 months expressed more c-MYC and enhanced resistance 30 . Upon comparison with the models produced in this study, much less concentrations of tamoxifen were used with no significant c-MYC gene expression and over expressed GLUL was observed.…”
Section: Discussionmentioning
confidence: 99%
“…In the cell cycle arrest, E 2 play a relevant role in resistance induction since some reports indicate that the ERα stimulates cell cycle progression through positive transcriptional regulation of cyclin D, since ERα interacts to an AMPc-response element (CRE) present in the cyclin D gene promoter, and induces the synthesis of the c-myc oncogene which controls the expression of cyclin D1 ( 70 ). The induction of c-Myc by E 2 is also generated by the binding of ERα to an ERE, present in the promoter region of the c-myc gene ( 60 , 71 ). The E 2 -ER rapidly activates the cyclin E/CDK2 complex accelerating the transition from G1 to S; furthermore, ER negatively regulates the expression of the p21 inhibitor to induce the progression of the cell cycle ( 72 ).…”
Section: Estrogens Induce Resistance By Inhibiting Apoptosismentioning
confidence: 99%